Social audit of the training function in institutions: A case study of the GICA cement company, Bouziane branch - Nabti, Hind; Fayçal, Krim; Abdelmadjid, Mezhoud (Art Law and Accounting Reporter, 2025)
This study aims to use social auditing to evaluate and analyse the effectiveness of the training function at the GICA cement company's Hamma Bouziane branch, while examining future developments in training indicators by forecasting them for the period 2024-2026 using the POWER BI programme. The descriptive analytical approach was used as a basis for covering the theoretical aspects and collecting and analysing data related to training programmes and their effectiveness during the period 2018-2023. The study concluded that social auditing revealed clear disparities in the performance of the training function and structural problems in the design and implementation of training programmes that call for strategic intervention and a re-engineering of training policy. This audit was not limited to the current diagnosis, but also extended to future forecasting, showing that effectiveness indicators stabilised at 79%, below the target standard for the period from 2024 to 2026, confirming its role as an effective diagnostic and forecasting tool for improving human resource management and developing institutional performance.
Keywords: social audit; human resource management; formation audit; prediction